Perubahan Bentuk Komoditi Unggulan Lokal Sebagai Alternatif Usaha di Desa Pringgarata - Suparmin Suparmin; Halimatus Sa’diyah; Anas Zaeni; Tajidan Tajidan (Universitas Mataram, 2020)
This community service activity was carried out in Pringgarata Village, Pringgarata District, Central Lombok Regency in August 2019. This community service activity uses field learning methods which are strengthened by demonstrations of local commodity development and assisted by experts processing soybeans into soy milk and dregs. soybeans become naget. Based on the results of community service activities regarding agro-industrial development based on local commodities, it can be concluded that: 1) The extension participants have given positive responses to all stages of the activity which is indicated by the seriousness of the participants in listening and discussing existing problems and participating actively in the demonstration of making agro-industry products, 2) In general, extension participants have acquired knowledge and skills in producing from agro-industry unit products, and 3) The next suggestion is to help increase household income at extension sites and at the same time encourage farmers to provide raw materials for agro-industrial development hence an active role from the government and related parties in policy makers is needed to implement a model of income generation program through community empowerment that has been carried out through activities outreach